Vascular Cognitive Disorder - Paradise, Matt B.; Sachdev, Perminder S. (Seminars in Neurology, 2019)
The term vascular cognitive disorder (VCD) refers to a heterogeneous group of disorders in which the primary feature is cognitive impairment attributable to cerebrovascular disease (CVD). This includes not only vascular dementia (VaD) but also cognitive impairment of insufficient severity to meet diagnostic criteria for dementia. VCD is recognized as the second most common cause of dementia after Alzheimer's disease (AD), but prevalence rates vary widely according to the diagnostic criteria employed. There have been recent attempts to standardize diagnostic criteria. VCD incorporates a range of neuropathological mechanisms including poststroke impairment, small and large vessel disease, and cases of mixed-pathology, with CVD interacting with AD and other neuropathologies. Recent neuroimaging data have improved our understanding of the etiology of VCD. Symptomatic treatments for VaD have modest benefit and there is increased focus on the primary and secondary preventative benefits of vascular risk factor control.
Keywords: vascular dementia; vascular cognitive disorder; cerebrovascular disease; small vessel disease